Microglial Activation Is Modulated by Captopril: in Vitro and in Vivo Studies - Asraf, Keren; Torika, Nofar; Apte, Ron N.; Fleisher-Berkovich, Sigal (Frontiers in Cellular Neuroscience, 2018)
The renin-angiotensin system (RAS) is an important peripheral system involved in homeostasis modulation, with angiotensin II (Ang II) serving as the main effector hormone. The main enzyme involved in Ang II formation is angiotensin-converting enzyme (ACE). ACE inhibitors (ACEIs) such as captopril are predominantly used for the management of hypertension. All of the components of the RAS have also been identified in brain. Centrally located hormones such as Ang II can induce glial inflammation. Moreover, in Alzheimer’s disease (AD) models, where glial inflammation occurs and is thought to contribute to the propagation of the disease, increased levels of Ang II and ACE have been detected. Interestingly, ACE overexpression in monocytes, migrating to the brain was shown to prevent AD cognitive decline. However, the specific effects of captopril on glial inflammation and AD remain obscure. In the present study, we investigated the effect of captopril, given at a wide concentration range, on inflammatory mediators released by lipopolysaccharide (LPS)-treated glia. In the current study, both primary glial cells and the BV2 microglial cell line were used. Captopril decreased LPS-induced nitric oxide release from primary mixed glial cells as well as regulating inducible nitric oxide synthase expression, nitric oxide, tumor necrosis factor- alpha and induced interleukin-10 production by BV2 microglia. We further obtained data regarding intranasal effects of captopril on cortical amyloid β (Aβ) and CD11b expression in 5XFAD cortex over three different time periods. Interestingly, we noted decreases in amyloid betaburdenin captopril-treated mice over time which was paralleled by increased microglial activation. These results thus shed light on the neuroprotective role of captopril in AD which might be related to modulation of microglial activation.